An Indirect Impact of Sika Deer Overpopulation on Eutrophication of an Aquatic Ecosystem via Understory Vegetation: An Individual-Based Approach Using Nitrate Reductase Activity - Tsuboike, Yasuo; Fujii, Masanori; Yoshida, Yumiko; Kamata, Naoto (Frontiers in Ecology and Evolution, 2021)
Eutrophication of aquatic ecosystems is a serious global issue. Stream nitrate concentrations at the University of Tokyo Chichibu Forest have increased since 2000 after the opening of the new highway in 1998. Nitrogen oxide emissions from automobile exhausts were the most likely source of increased nitrate input in the forest ecosystem. Around the area, the sika deer Cervus nippon Temminck population has greatly increased since around 2000 and intensively browsed the understory vegetation. We hypothesized that the degradation of the understory vegetation caused by the deer overpopulation was one of the causes of increased nitrate output. Monthly observations were carried out from April to October 2013 to investigate the understory vegetation at the heights of 0–30 and 100–150 cm above the ground inside (without deer) and outside (with deer) of a deer exclusion fence. Plant taxa and % coverage of each taxon at each layer were recorded. The in vivo nitrate reductase activity (NRA) (≈ nitrate assimilation rate) was determined for each plant taxa each month. Compared to inside the fence, the understory vegetation outside was poor with smaller % coverage and less diverse community structure, and was occupied by unpalatable plant taxa that were uncommon or absent inside the fence. Contrary to our expectation, the phylogenetic diversity of the community assemblage outside the fence showed greater evenness (less clustering) than inside. The NRA peaked in early in the season or late in the season. In contrast to a previous report, no significant difference in the NRA was found between woody and herbaceous plants. Although the difference was no more than that of vegetation coverage, the estimated community-level NRA inside the fence was 5.6 times higher than that of the outside. The difference was greatest early in the season. These results support our hypothesis.